COVID-19 and the Political Framing of China, Nationalism, and Borders in the U.S. and South Korean News Media. (October 2021) - Chung, Angie Y.; Jo, Hyerim; Lee, Ji-won; Yang, Fan
Using an inductive framing analysis of news coverage, we examine how the most popular liberal and conservative news media in the United States and South Korea mobilize different nationalist narratives on China in responding to social, economic, and political upheavals during the early stages of the COVID-19 pandemic. We identify three major areas of political cleavage in both Korean and U.S. media discourse on nationalist identities vis-à-vis the construction of the national or racialized "Other." This includes (1) imagined solidarity against China as an adversary; (2) political disputes over boundary-making; (3) and the construction of ethnonational belonging and exclusion. Our research underscores how intrastate and interstate shifts during periods of crisis can heighten political cleavages along racial and ethnic fault lines and complicate dominant frameworks of civic and ethnic nationalism in both countries.